SURGICAL TREATMENT OF SEVERE RUMINAL IMPACTION AND DYSTOKIA IN BEETAL GOAT - FAROOQ, AA; MURTAZA, S; AHMAD, E; LASHARI, MH; JAVID, MA; SALEEM, MU; BASIT, MA; WAQAS, MY; ASIF, M; SHAH, MH; et al. (Biological and Clinical Sciences Research Journal, 2024)
An orgasmic, restless, and persistently bloated female goat, approximately 22–24 months of age, was taken to the outdoor clinic of the Department of Clinical Sciences, Faculty of Veterinary Sciences, Bahauddin Zakariya University, Multan. The goat had a history of of pregnancy about four and a half months. Upon physiological examination, the rectal temperature was within normal limits; nevertheless, the heart rate and breathing rate showed modest deviations towards lower limits. The oral and conjunctival mucous membranes were congested, as shown by a physical examination. On abdominal palpation, a hard, mass was felt in the rumen (anterior abdomen). In addition, ultrasonography showed that two dead fetuses were present in the right uterine horn. Moreover, further scanning showed a hyperechoic area (D=5cm) in the rumen. A tentative diagnosis of impaction and dystocia was made based on the clinical evaluation and ultrasonography. An exploratory rumenotomy and hysterectomy were recommended after diagnosis. upon rumenotomy, the rumen was packed with 1.5 kg of calcified masse. It was composed of compressed foreign bodies ( plastic bags and rope). The surgery was performed according to standard protocol. The animal healed without incident after receiving parental antibiotics (Oxytetracycline @ 5 mg/kg), NSAIDs (Meloxicam 0.5-1 mg/kg), and fluids (NS & RL) for seven days following surgery.